SUBTILUSI MINYAK SAWIT MERAH DAN TEPUNG TEMPE SEBAGAI SUMBER VITAMIN A PADA PRODUK COOKIES - Vanda Julita; Evy Damayanti (Universitas Riau, 2002)
An observation concerning tiic making use of Red Palm Oil (RPO) as a source of B-caroten in cookies production was carried out. The formula was a modification of a research carried out by Rimbawan et al (1995). The analysis result of R-caroten content in the product are; cookies with maizcna as a natural substance with concentration of RPO 40%, 60% and 80% respectively are in amount of 9290 ng, 12360.25 /tg and 28503.4 ng; cookies with rice flour and conscntration of RPO 40%, 60% and 80% respectively arc in amount of 8532 /tg, 23760 ftg and 29408 /tg per 100 gram successively. Average consumption of cookies as such much as 20 g/day increased vitamin A as amount 999.6 RK for cookies rice flour with consentration RPO 80% and 414,4 R E for cookies maizcna with consentraliun RPO 60%.